A study comparing the prescribing pattern of antibiotics for fever between Dhaka City and different villages in Bangladesh - Shuchi, Noshin Sayiara (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.